The Influence Of Work-Life Balance And Motivation On Employee Performance: A Case Study At The Faculty Of Medicine, North Sumatera University, With Job Satisfaction As A Mediator - Margolang, Rizka Khairunnisa (AIBPM Publisher, 2024)
In the era of globalization and the industrial revolution 4.0, improving human resources quality becomes crucial in achieving organizational success. Human resource management (HRM) plays a crucial role as it significantly contributes to organizational goals. Each individual within the organization is a valuable investment, as their potential can be optimally utilized to achieve success. Therefore, HRM must be carried out carefully and effectively. Employee performance also plays a key role in the operational aspects of educational institutions and significantly influences organizational goals. Employee performance at the Faculty of Medicine, North Sumatera University, is a crucial factor in achieving academic organizational objectives. This study aims to identify factors influencing employee performance, namely Work-Life Balance, Motivation, Organizational Culture, and Job Satisfaction. The research method used is associative causal research with a quantitative approach. The research sample consists of 99 employees selected using total sampling method. Data were collected through interviews, documentary studies, and questionnaires. The analysis results indicate that Motivation has a significant positive influence on Job Satisfaction, while Work motivation has a significant positive influence. Work-Life Balance has a significant positive influence on Employee Performance, but Work motivation has a significant positive influence on Employee Performance. Additionally, Job Satisfaction has a significant positive influence on Employee Performance. Recommendations from this study include the management of the Faculty of Medicine, North Sumatera University, paying attention to employee Work-Life Balance and strengthening positive organizational culture. Providing incentives or rewards to employees who achieve high job satisfaction levels is also suggested to enhance overall performance.Keywords: Work-Life Balance, Motivation, Employee Performance, Job Satisfaction